PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA SEKTOR RITEL ELEKTRONIK TAHUN 2013-2022 - Gusti Hermawan; Dewi Nari Ratih Permada (Journal of Research and Publication Innovation, 2024)
The purpose of this study is to determine the effect of the Current Ratio and Debt to Equity Ratio, together, on the Return on Assets of retail electronics companies from 2013 to 2022, using a descriptive associative method with a quantitative approach. The type of data used is secondary data obtained from the financial statements of retail electronics companies for the period 2013-2022 from the websites www.idx.co.id, www.corp.electronic-city.com, www.erajaya.com, and www.map.co.id. Data analysis involves descriptive testing, classical assumption tests including normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, coefficient of determination (R2) analysis, and hypothesis testing including partial test (t-test) and simultaneous test (F-test). Data processing uses Eviews version 13.The results show that the Current Ratio, when tested partially, does not have a significant effect on Return on Assets. This is evident from the test result where the t-value is 0.287898 < t-table 2.051831 and the probability value is 0.7758 > 0.05, meaning Ho1 and Ha2 are rejected. The results also show that the Debt to Equity Ratio, when tested partially, has a significant effect on Return on Assets. This is indicated by the absolute t-value of -3.683811 > t-table 2.051831 and the probability value of 0.0011 < 0.05, meaning Ho2 and Ha3 are accepted. Additionally, the Current Ratio and Debt to Equity Ratio together have a significant simultaneous effect on Return on Assets, as shown by the F-value of 5.100720 > F-table 3.35 and the probability value of 0.003814 < 0.05. The coefficient of determination (R2) for this study is 36.12%. There are other factors not considered in this regression model, accounting for 63.86%.